2015
DOI: 10.1080/10255842.2015.1052419
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional macro-scale assessment of regional and temporal wall shear stress characteristics on aortic valve leaflets

Abstract: The aortic valve (AV) achieves unidirectional blood flow between the left ventricle and the aorta. Although hemodynamic stresses have been shown to regulate valvular biology, the native wall shear stress (WSS) experienced by AV leaflets remains largely unknown. The objective of this study was to quantify computationally the macro-scale leaflet WSS environment using fluid-structure interaction modeling. An arbitrary Lagrangian-Eulerian approach was implemented to predict valvular flow and leaflet dynamics in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 40 publications
3
32
0
5
Order By: Relevance
“…Moreover, the averaged OSI across the entire aortic valve surface was previously reported to be an OSI ~0.16 [41] which is close to the "sweet spot" OSI range (0.18-0.23) of the current study. However, we note that fluid-induced oscillations are considerably greater on the fibrosa surface as compared to the ventricularis surface and as a result, regional OSI can vary.…”
Section: Discussion Of Specific Aimsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the averaged OSI across the entire aortic valve surface was previously reported to be an OSI ~0.16 [41] which is close to the "sweet spot" OSI range (0.18-0.23) of the current study. However, we note that fluid-induced oscillations are considerably greater on the fibrosa surface as compared to the ventricularis surface and as a result, regional OSI can vary.…”
Section: Discussion Of Specific Aimsupporting
confidence: 87%
“…The bioreactor system which we utilized is able to mimic regionally varying shear stresses on the specimen surfaces and is analogous to native tri-leaflet heart valve shear stress distributions [25]. Indeed, the range of OSI (0.18 -0.23) identified here is closeto the typical OSI experienced by aortic valve tissues (OSI ~ 0.16) [41]. Previous studies on Flex-Flow conditions by [5] and [6] found that the 3-dimensional coupling of cyclic flexure, cyclic stretch and fluid-induced shear stresses manifest as oscillatory patterns surrounding the localized flow field of the heart valve leaflets.…”
Section: Discussion Of Specific Aimmentioning
confidence: 68%
See 1 more Smart Citation
“…Compared with mechanical valve replacements, compliant aortic valves, such as tissue-engineered bioprosthetic valves and polymeric valves, have soft leaflets that could result in better hemodynamics. The fluid dynamics and fluid-structure interaction (FSI) of bioprosthetics and native tissue aortic valves have been studied extensively in computational fluid dynamics and fluid-structure interaction simulations [22][23][24][25]. The dynamic responses of the soft valve leaflets under simulated physiological loadings have been studied by many finite element simulations [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the proximal ascending aorta produces native regions of oscillatory shear stress. Endothelial cells on the aortic side of the aortic valve are normally subjected to oscillatory shear stress after the valves close, and a loss of this oscillatory stress results in expression of adhesion proteins and cytokines consistent with endothelial activation [23, 24]. Cathepsin expression by endothelial cells are ultimately regulated by this complex inflammation cascade and altered biomechanical hemodynamic signaling [15, 16, 25, 26].…”
Section: Introductionmentioning
confidence: 99%